Colloid carcinoma derived from intraductal papillary mucinous neoplasm of the pancreatic head with calcification: A case report and literature review - Ryoichi Miyamoto (Surgical Case Reports, 2021)
Abstract Background Colloid carcinoma derived from intraductal papillary mucinous neoplasm (IPMN) of the pancreatic head with prominent calcification is exceedingly rare. Only a few studies about this entity have been reported in the literature. Therefore, its biological behavior, appropriate treatment modalities, and overall patient prognosis remain largely unclear. In this report, we present a case of a resected colloid carcinoma derived from IPMN with prominent calcification. In addition, we review the relevant literature and discuss the clinical management of colloid carcinoma derived from IPMN with prominent calcification, including the histopathological features. Case presentation A 75-year-old man presented with a pancreatic tumor measuring 58 mm on the head of the pancreas that was incidentally detected by abdominal ultrasonography. Abdominal computed tomography and endosonography revealed a multilobular cystic lesion with a 17 mm mural nodule in the pancreatic head. Furthermore, prominent calcification was observed on part of the cyst wall. Magnetic resonance cholangiopancreatography showed a multilobular cyst in the branch duct lacking communication between the cystic lesion and the main pancreatic duct. Thus, the lesion was diagnosed as intraductal papillary mucinous carcinoma (IPMC) with a preoperative classification of T1N0M0 stage IA according to the 8th Union for International Cancer Control (UICC) guidelines, and the patient underwent conventional pancreatoduodenectomy. The resected specimen was microscopically found to contain colloid carcinoma, probably derived from IPMN. In addition, marked calcification was confirmed in the partition wall of the cystic mass. The postoperative course was uneventful, and no evidence of recurrence or metastasis was observed after 10 months of follow-up. Conclusions We consider that colloid carcinoma derived from IPMN should be differentially diagnosed as a pancreatic multilobular cystic lesion with prominent calcification that shows no sign of systemic chronic pancreatitis.